Success within a UK open prison and surviving the ‘pains of freedom’ - Statham, Bethany May (Psychology, crime & law, 2021)
Category D open prisons mark a critical juncture of a prisoner’s sentence as they near the end of imprisonment and reach the cusp of release. Such establishments aim to support prisoner re-entry by offering greater freedom and autonomy. A greater understanding of the reality of life within an open establishment and exactly how these conditions support prisoner re-entry is needed. This study is made up of interviews with 11 prisoners residing in a UK open prison. Interviews were analysed qualitatively using interpretative phenomenological analysis which revealed two superordinate themes: ‘redemption through active citizenship’ and ‘coping with invisible boundaries’. These themes are unpacked and their relevance to prisoner re-entry are discussed. The study found that greater freedom and autonomy encouraged reciprocal support amongst residents. Participants discuss strategies they utilise to help them to cope with the ‘pains of freedom’. Implications for supporting individuals in their transformation from prisoner to citizen within an open establishment are highlighted and suggestions for future research offered.